Chroboty, echa, oho! Słuch i inne zmysły w poezji Mirona Białoszewskiego - Kopkiewicz, Aldona (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The very relation between possibility of writing and sensitivity is a main concern of this interpretation of Miron Białoszewski’s poetry. At the start, I notice traumatic state of writing subjectivity, which I see as a negative affect. Białoszewski’s trauma manifests itself as an acedia in the Leżenia poetry cycle, in which the poet searches for another, positive affective simulation as well. He finds it in the very work of language, of sounds, and of material reality surrounding him. As he tries to revive himself and his writing mainly through the senses of touching and hearing/listening, I use the model of subjectivity described by Jean-Luc Nancy in the essay On listening, to understand how creative, writing subjectivity works on sensual and language levels.